2012
DOI: 10.3109/09638288.2012.715719
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hybrid cycle training in inactive people with long-term spinal cord injury: design of a multicenter randomized controlled trial

Abstract: The results of this RCT may provide future implications for exercise prescription that preserve long-term functioning in people with SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…The production and release of IL-6 is regulated by a synergy of signaling pathways responsive to mechanical stimuli, intramuscular calcium concentrations, muscle glycogen stores, and the sympathetic nervous system (SNS) [3,12,21]. In support of previous findings, 30 min of moderate intensity upper-limb exercise alone resulted in a significant increase in SNS-mediated plasma adrenaline concentrations [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Despite this SNS response, the 0.5-fold increase in plasma IL-6 observed during HC was smaller than the IL-6 response previously reported by Kouda et al in a group of non-spinal injured controls during 20 min arm-crank ergometry at the same relative intensity [9].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The production and release of IL-6 is regulated by a synergy of signaling pathways responsive to mechanical stimuli, intramuscular calcium concentrations, muscle glycogen stores, and the sympathetic nervous system (SNS) [3,12,21]. In support of previous findings, 30 min of moderate intensity upper-limb exercise alone resulted in a significant increase in SNS-mediated plasma adrenaline concentrations [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Despite this SNS response, the 0.5-fold increase in plasma IL-6 observed during HC was smaller than the IL-6 response previously reported by Kouda et al in a group of non-spinal injured controls during 20 min arm-crank ergometry at the same relative intensity [9].…”
Section: Discussionsupporting
confidence: 73%
“…The addition of FES-evoked cycling to concurrent upper-limb exercise, termed hybrid exercise (HYB), has been shown to elicit greater cardiorespiratory stress than arm exercise alone [17]. Via the activation of a larger muscle mass, HYB may provide a more effective method for improving cardiorespiratory fitness and reducing risk factors for CVD than traditional upper-limb exercise modes [18]. It is unknown whether the deterioration in skeletal muscle size [19] and alterations in skeletal muscle metabolism [20] observed following lower-limb paralysis will affect the release of IL-6 and the subsequent anti-inflammatory cascade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of the current study (which is part of a larger study) has been described previously by Bakkum et al (18). Briefly, this study was a 16-week open, explanatory, parallel-group randomized controlled trial (RCT), performed in 2 Dutch rehabilitation centres with a specialized SCI unit.…”
Section: Trial Designmentioning
confidence: 99%
“…Ebrahimi Hand bike is another alternative to the conventional, manually propelled wheelchairs. Longitudinal studies and multicenter randomized clinical trials have confirmed that regular hand cycling training has a positive influence on aerobic physical capacity and muscle strength, without reported shoulder pain [63][64][65].…”
Section: Alternative Propulsion Methodsmentioning
confidence: 95%